2015
DOI: 10.1016/j.fertnstert.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian hormone as a predictor of good-quality supernumerary blastocyst cryopreservation among women with levels <1 ng/mL versus 1–4 ng/mL

Abstract: Low AMH levels are associated with a statistically significantly lower likelihood of blastocysts for cryopreservation as compared with higher AMH levels. This effect was seen among women both <35 and ≥35 years of age. Patient counseling should include realistic expectations for the probability of good-quality supernumerary blastocysts available for cryopreservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
8
1
1
Order By: Relevance
“…There is an association between AMH and oocyte yield after ovarian stimulation, and the hormone has been shown to be a strong predictor of ovarian response to gonadotropins, whether satisfactory, poor or excessive, cycle cancellation, and of the quality of oocytes and embryos (La Marca et al ., 2005; Kavoussi et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…There is an association between AMH and oocyte yield after ovarian stimulation, and the hormone has been shown to be a strong predictor of ovarian response to gonadotropins, whether satisfactory, poor or excessive, cycle cancellation, and of the quality of oocytes and embryos (La Marca et al ., 2005; Kavoussi et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As previously explained, many published studies have described the clinical application of AMH measurement in the prediction of both, quantitative and qualitative ovarian response in ART [29]. There is an association between AMH and oocyte yield after ovarian stimulation, and the hormone has been shown to be a strong predictor of ovarian response to gonadotropins [17,27,39]. However, patients with undetectable AMH levels have been shown to successfully obtain oocytes at the time of retrieval and even to achieve ongoing pregnancy [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating embryo quality, Kavoussi et al [ 38 ] reported that regardless of age, low serum AMH levels (<1 ng/mL) were associated with a significantly lower availability of high-quality blastocysts for cryopreservation than was observed in patients with higher AMH levels (1–4 ng/mL) in IVF cycles.…”
Section: Ovarian Reserve Markersmentioning
confidence: 99%